2015
DOI: 10.1071/rd14024
|View full text |Cite
|
Sign up to set email alerts
|

Open pulled straw vitrification and slow freezing of sheep IVF embryos using different cryoprotectants

Abstract: The aim of the present study was to evaluate the post-thaw survival and hatching rates of sheep blastocysts using different cryoprotectants. In Experiment 1, Day 6 sheep embryos were cryopreserved by a slow freezing protocol using 10% ethylene glycol (EG), 10% dimethyl sulfoxide (DMSO) or a mixture of 5% EG and 5% DMSO. Hatching rates were higher in the 10% EG group than in the 10% DMSO or EG + DMSO groups (30% vs 18% and 20%, respectively). In Experiment 2, embryos were cryopreserved by open pulled straw (OPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Thus, the results of the present study, using both traditionally accepted slow freezing and ultra-fast vitrification for embryo cryopreservation show that embryo quality was good with both techniques. The results of our study are consistent with those obtained by other researchers [45,46], in which the quality of frozen-thawed embryos was higher with vitrification procedures than with the slow-freeze method [47,48]. The advantages of using vitrification for embryo cryopreservation are simplicity, rapidity of the procedure and the fact that this method does not require expensive equipment as in the case of the slow freezing method.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the results of the present study, using both traditionally accepted slow freezing and ultra-fast vitrification for embryo cryopreservation show that embryo quality was good with both techniques. The results of our study are consistent with those obtained by other researchers [45,46], in which the quality of frozen-thawed embryos was higher with vitrification procedures than with the slow-freeze method [47,48]. The advantages of using vitrification for embryo cryopreservation are simplicity, rapidity of the procedure and the fact that this method does not require expensive equipment as in the case of the slow freezing method.…”
Section: Discussionsupporting
confidence: 92%
“…Following Bhat et al [15], 10% of the best-quality early blastocysts of each experimental group were vitrified using the open pulled straw (OPS) technique [16], which consisted of washing the blastocysts in 800 µL of holding medium (TCM-199 without HEPES, supplemented with 10% FBS). They were then sequentially equilibrated, first in 600 µL of holding medium supplemented with 7.5% of ethylene glycol and 7.5% of DMSO for 3 min, then in 600 µL of holding medium with 0.342 g/mL of sucrose, 16.5% of ethylene glycol, and 16.5% of DMSO for 20 s. Immediately afterwards, 2 µL drops were formed with the embryos and collected by capillarity in an OPS.…”
Section: Vitrification and Devitrification Of Embryosmentioning
confidence: 99%
“…Caprine embryos have been shown to present better viability after the vitrification process than after controlled-rate slow freezing [73][74][75]. On the other hand, studies performed in equine and donkey embryos showed that controlled-rate slow freezing seemed to be the most appropriate cryopreservation method [76,77].…”
Section: Controlled-rated Slow Freezing Versus Vitrification: Advanta...mentioning
confidence: 99%